2006
DOI: 10.1073/pnas.0601309103
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of specific RNA interference-mediated silencing of human β-globin alleles differing by a single nucleotide polymorphism

Abstract: sickle cell anemia ͉ specificity of silencing ͉ hemoglobin E ͉ hemoglobin S

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 24 publications
2
33
0
Order By: Relevance
“…18,19 Unfortunately, these rules do not apply the same to different targets. For example, a C:A mismatch at the tenth position did not affect gene silencing, 26 resulted in target knockdown of only approximately 25% 18 or as shown in our study was not tolerated at all. If this also applies for a G:U mismatch at the tenth position was not investigated in this particular studies.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…18,19 Unfortunately, these rules do not apply the same to different targets. For example, a C:A mismatch at the tenth position did not affect gene silencing, 26 resulted in target knockdown of only approximately 25% 18 or as shown in our study was not tolerated at all. If this also applies for a G:U mismatch at the tenth position was not investigated in this particular studies.…”
Section: Discussionmentioning
confidence: 97%
“…This is in line with the observation that RNAi is lost upon introduction of central mismatches (positions 9-11). [13][14][15][16][17][18][25][26][27] The catalytic site is at that region and apparently loss of proper base pairing at those specific positions results in loss of RNAi. This was strengthened by the finding that the same mismatches (C:A and G:U) at the seventh position in the AS strand were tolerated.…”
Section: Discussionmentioning
confidence: 99%
“…For example, SNPs involving purine:purine antisense:target mismatches with the wild-type allele (ie, G:A, G:G, A:A and A:G) will tend to provide the most allele-specific results. 6,7 Conversely, pyrimidine:pyrimidine, pyrimidine:purine or purine:pyrimidine mismatches are expected to be well accommodated in the antisense moleculemRNA helix and, therefore, display only intermediate levels of discrimination. Of these, the least prone to allele-specific silencing are C:A, U:G, C:U and U:U 6 .…”
Section: Resultsmentioning
confidence: 99%
“…Second, only some of the sequences containing the SNPs have the molecular features necessary for potent allele-specific gene silencing. 6,7,8,9,10 Therefore, the future set of guidelines for the gene therapy of these diseases will presumably require iteration from bioinformatics to empirical validation. In this context, taking into account putative targets with their degrees of heterozygosity, haplotype structures across populations and molecular constraints for gene therapy could provide valuable information to facilitate the empirical validation of new allele-specific therapies and predict their performances outside the genotyped sample across different population groups.…”
Section: Introductionmentioning
confidence: 99%
“…Since these original discoveries the rules determining successful mRNA suppression by siRNAs have been extensively studied and siRNAs are now invaluable tools for studies of partial gene knockout in vitro as well as in vivo [14]. Studies of siRNAs that discriminate between single nucleotide variants within mRNAs have shown that allele specific silencing utilizing siRNA technology is possible [15][16][17][18][19][20]. This suggests that siRNAs may be a way forward in the treatment of dominant monogenetic diseases, such as OI.…”
Section: Ivyspringmentioning
confidence: 99%